PEMANFAATAN TEPUNG DAUN KELOR (Moringa oleifera) DALAM FORTIFIKASI NUGGET ITIK SERATI - Masruroh, Masruroh; Herliani, Herliani; Habibah, Habibah (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2024)
This research was conducted to determine the level of preference of the panelists with the addition ofMoringa leaf flour on the quality of color, taste, texture of Serati duck nuggets. This research methodused a completelyrandomized design (CRD) with five treatments and four repetitions totaling 20 trialsconsisting of: (P0) duck meat 250 g + wheat flour 100 g, (P1) duck meat 250g + wheat flour 90 g +moringa leaf flour 10 g, (P2) duck meat 250 g + wheat flour 80 g + moringa leaf flour 20 g, (P3) duckmeat 250 g + wheat flour 70 g + moringa leaf flour 30 g and (P4) duck meat 250 g + wheat flour 60 g+ moringa leaf flour 40 g. Data were analyzed using analysis of variance (Anova/Analysis OfVariance), if the results show an effect then proceed with the DMRT test (DuncanMultiple Range Test)at 5% level. Statistical analysis was performed using SPSS version 21 software (IBM, USA). The resultsshowed that the addition of moringa leaf flour to the Serati duck nuggets with had a significant effect(P<0,05) on color, taste and texture.